Speech text of launching of digital certification partnership initiative between Universiti Teknologi MARA (UiTM), International Certification of Digital Literacy (ICDL), and NAMA Foundation / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
I am delighted to be here to witness the official beginning of UiTM's collaboration with the International Certification of Digital Literacy (ICDL) and the NAMA Foundation, both of whom are leaders in their respective fields. 5. Congratulations and thank you to all committee members from the Faculty of Business and Management (FBM) for their hard work in putting this event together as well as for inviting me today.